Vietnamese Phở Restaurant Choices: Halal Culinary Lifestyle in the People of Jakarta-West Java-Banten - Marissa Grace Haque (CV. Syntax Corporation Indonesia, 2024)
Vietnamese restaurants in Jakarta, West Java, Banten Provinces are growing quite rapidly. Along with the immediate implementation and threat of sanctions from halal guarantee regulations in Indonesia based on Law No. 33 of 2014, followed by PP No. 31 of 2019, and it is now converted into Law No. 11 of 2020 and Law No. 6 of 2023 concerning Stipulation of Government Regulations in Lieu of Law no. 2 of 2022 concerning Job Creation Becomes Law. There are two types of Vietnamese restaurants in Indonesia: (1) with the Indonesian halal logo; and (2) does not have any. The aim of this research is to find out whether there is an influence of consumer awareness and knowledge, the Indonesian halal logo, and religiosity on purchasing decisions at Vietnamese restaurants, as well as the lifestyle of the people. Research Design/Method uses the SEM PLS, to determine the testing sample, describes it using a descriptive and verification approach, explaining the the cause and effect relationship between variables. Results show that the Indonesian Muslims in three selected provinces stated that their decision to enjoy in Vietnamese restaurants had a significant influence both in terms of their religiosity and the Indonesian halal logo. The awareness and knowledge variables have the smallest and insignificant influence on purchasing decisions that influence lifestyle. Discussion: It is an urgent situation in Indonesia to accelerate the socialization of its halal guarantee, before many victims fall due to have violated the Halal Product Guarantee regulations in Indonesia, with criminal sanctions imposed.